The p53–Mdm2 interaction and the E3 ligase activity of Mdm2/Mdm4 are conserved from lampreys to humans - Venkatesh, Byrappa (2016)
The extant jawless vertebrates, represented by lampreys and hagfish, are the oldest group of vertebrates and provide an interesting genomic evolutionary pivot point between invertebrates and jawed vertebrates. Through genome analysis of one of these jawless vertebrates, the Japanese lamprey (Lethenteron japonicum), we identified all three members of the important p53 transcription factor family—Tp53, Tp63, and Tp73—as well as the Mdm2 and Mdm4 genes. These genes and their products are significant cellular regulators in human cancer, and further examination of their roles in this most distant vertebrate relative sheds light on their origin and coevolution. Their important role in response to DNA damage has been highlighted by the discovery of multiple copies of the Tp53 gene in elephants. Expression of lamprey p53, Mdm2, and Mdm4 proteins in mammalian cells reveals that the p53–Mdm2 interaction and the Mdm2/Mdm4 E3 ligase activity existed in the common ancestor of vertebrates and have been conserved for >500 million years of vertebrate evolution. Lamprey Mdm2 degrades human p53 with great efficiency, but this interaction is not blocked by currently available small molecule inhibitors of the human HDM2 protein, suggesting utility of lamprey Mdm2 in the study of the human p53 signaling pathway.